Leveraging Social Media for Improved Writing in English as a Foreign Language - Azzahra, Rona Nur; Nor, Hidayah; Mufidah, Nida (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
In the contemporary digital era, social media constitutes a significant and pervasive element of students' daily experiences, especially within the domain of foreign language acquisition. This qualitative narrative inquiry sought to comprehensively explore the nuanced effects of various social media applications on the writing abilities of English as a Foreign Language (EFL) students enrolled at Universitas Islam Negeri Antasari, Banjarmasin. This study focused on three English education students who were chosen because they actively use social media and are learning English as a Foreign Language (EFL). Researchers gathered information through in-depth, semi-structured interviews and narrative frameworks to understand their personal experiences. The data were analyzed using narrative analysis to find common themes and important insights. The results show that popular social media platforms like Instagram, TikTok, and Twitter help students improve their writing. Students gained more vocabulary, felt more confident expressing themselves in English, and saw real examples of English in different situations. Still, the study found some downsides, including students using more informal language, having fewer opportunities for face-to-face interaction, and spending too much time on their phones. The study concludes with teaching suggestions that offer ways to make the most of social media’s benefits while reducing its negative effects in EFL writing classes.